Synthesizing contracts correct modulo a test generator. - Astorga, Angello.; Saha, Shambwaditya.; Dinkins, Ahmad.; Wang, Felicia.; Madhusudan, P.; Xie, Tao. (Tufts University. Tisch Library., 2023)
Keywords: Data-Driven Inference, Software Testing, Specification Mining, Synthesis.; Topic: Theory of computation / Semantics and reasoning / Program reasoning / Program specifications; Topic: Software and its engineering / Software organization and properties / Software functional properties / Formal methods / Dynamic analysis; Topic: Computing methodologies / Machine learning / Machine learning approaches / Classification and regression trees; ACM Open.